Cone-Beam Computed Tomography to Assess Mandibular Invasion in Oral Squamous Cell Carcinoma (Update Dental College Journal, 2018)
Background: Oral squamous cell carcinoma which occurs closely to the mandible has a tendency to invade mandible. An accurate preoperative evaluation of mandibular invasion is important for optimum treatment planning. Aim of this study is to determine the accuracy of CBCT in detection of mandibular invasion in oral squamous cell carcinoma.Study design: In this prospective observational study 35 patients of histologically proven squamous cell carcinoma which was close proximity to the mandible were selected. The results of preoperative CBCT scan of mandible were compared with that of post operative histopathology of bone and thus sensitivity, specificity, negative predictive value, positive predictive value were calculated.Results: Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of CBCT were 96%, 90.90%, 96%, 90.90%, 97.14% respectively (Chi squared with Yates correction equals 21.844 with 1 degrees of freedom, p value < o.oooo1).Conclusion: Cone beam computed tomography is a sensitive test and has an acceptable range of specificity.Update Dent. Coll. j: 2018; 8 (2): 18-22